An Ounce of Prevention: Conducting Effective Candidate Background Checks - Jonathan Kremser (Academic Chairpersons Conference Proceedings, 2020)
This session will address the often-overlooked component of the faculty search: effective background screening of short-listed applicants. Case studies of insufficient background checks will be discussed, and practical resources will be provided to participants that will help them avoid the endless energy draining task of managing conflict.
Keywords: Hiring; department management; applicant screening; faculty searches